Analisis Business Development Strategy Analysis of CV. Sehati Berkah Utama's Coffee Beans from an Islamic Economic Perspective - Liza Nurlaila; Sri Ramadhani; Juliana Nasution (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
A SWOT analysis is required to identify the strengths, weaknesses, opportunities, and threats that have been described in order to later increase CV. Sehati Berkah Utama's sales with market competition. The last sales at CV. Sehati Berkah Utama during the 2022–2024 period showed a significant increase in revenue. In order to boost sales at CV. Sehati Berkah Utama, this study attempts to identify company growth methods in Islamic economic studies by performing a SWOT analysis. Field research and literature study data types are used in this qualitative study's case study methodology. The business development plan utilized to boost sales at CV is the outcome of the data collection methods, which include data reduction, data presentation, and conclusion drafting. Shiddiq, Amanah, Fathanah, and Tabligh are the traits of the Prophet Muhammad SAW that form the foundation of Sehati Berkah Utama. And based on the theory and concept of Islamic business development strategies, it can be said that the business development plan in this Islamic economic study is appropriate.